The asymptotically safe standard model: from quantum gravity to dynamical chiral symmetry breaking - Pastor-Gutiérrez, Álvaro; Pawlowski, Jan M.; Reichert, Manuel (SciPost physics, 2023)
SciPost Journals Publication Detail SciPost Phys. 15, 105 (2023) The Asymptotically Safe Standard Model: From quantum gravity to dynamical chiral symmetry breaking
Gesehen am 29.01.2024